Correlating the prevalence of C174G polymorphism with IL-6, TNF-α and Hs-CRP in an elderly black South African population - Valentine, Jessica (Vaal University of Technology, 2019)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide, and the prevalence thereof is on the rise in developing countries due to the demographic transition and urbanization. The inflammatory process, atherosclerosis, is at the root of the majority of CVDs and is caused by unresolved inflammation. Various cardiovascular risk factors such as hyperglycaemia, dyslipidaemia, hypertension, smoking and aging stimulate the development of atherosclerosis through triggering inflammation. Being in a state of chronic low-grade inflammation therefor places an individual at higher risk of developing CVD, with inflammation playing a cause and effect role. The aim of this study was to investigate the inflammatory status of an elderly black South African population by analysis of inflammatory markers HS-CRP, TNF-α and IL-6, as well as the genetic polymorphism C174G associated with increased serum levels of IL-6 in some populations. The research was conducted in the field of Biomedical Sciences as a quantitative, cross-sectional, analytical observational design. The study was ethically approved and involved collection of 84 blood samples from volunteers in a purposively selected population as part of a larger collaborative study. Serum was used to analyse HS-CRP, TNF-α and IL-6 and DNA was extracted from whole blood for analysis of the C174G polymorphism. The median serum HS-CRP of 6.44mg/L (IQR = 2.82 - 9.86mg/L) fell within the highest risk (>5mg/L) of CVD and 75% of participants were at high (3.01-5mg/L) or very high (>5mg/L) risk. The median TNF-α of 0.00pg/mL was within the normal range and only 2.6% of participants had high serum TNF-α levels. The median serum IL-6 level was 1.92pg/mL and was also within the normal range with only 2.6% of participants who had high serum IL-6 levels. For the C174G polymorphism analysis, 98.6% had the GG, 1.4% the GC genotype and no participants had the CC genotype. The median serum IL-6 level of the homozygous GG group was 6.51mg/L, higher than the 4.13mg/L serum IL-6 of the heterozygous GC group. The difference in IL-6 should be considered with caution as only one participant had the C allele. A highly significant (p=0.001) correlation was found between HS-CRP and IL-6, as well as between IL-6 and TNF-α (p = 0.048). The elderly black Sharpeville community is in an increased inflammatory state which puts them at risk of CVD. The prevalence of the C allele in the C174G polymorphism is low in this population. Further research could be conducted as intervention studies to decrease the inflammatory state of the population and influence health policy changes to improve prevention of CVD.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Inflammation; HS-CRP. IL-6; TNF-α; C174G; Cardiovascular disease and elderly; Dissertations, Academic -- South Africa.; Cardiovascular diseases in old age.; Cardiovascular system -- Diseases.; Inflammation.